Heat Transfer Performance of Heat Pipe Radiator with SiO2/Water Nanofluids. Issue 7 (7th February 2017) - Shi, Jiyuan; Zhao, Weilin; Li, Jinkai; Liu, Zongming
Abstract: The effect of nanofluids on thermal performance of the miniature heat pipe radiator which was assembled by two heat pipes containing 0.6 vol.% SiO2 /water nanofluids and 30 pieces of rectangular aluminum fins was investigated experimentally and theoretically. The wall temperatures of the miniature heat pipe and fin surface temperatures were measured. Results showed that the utilization of SiO2 /water nanofluids as a working fluid in the heat pipe enhanced the heat performance by reducing wall temperature differences. Compared with Deionized water (DI water), the thermal resistance of the miniature heat pipe with SiO2 /water nanofluids decreased by about 23% to 40%. Furthermore, the theoretical calculation on a basis of one dimension found that the fin heat dissipation in the miniature heat pipe radiator charged SiO2 /water nanofluids was about 1.17 times of that of the DI water radiator.